Domestic violence and affectıng factors amongmarried women aged between 15-49 Years - Çifçi, Sema; Açık, Yasemin (My University, 2020)
Domestic violence against women is an important public health problem commonly encountered in all societies, manifesting itself as a negative outcome of gender inequality. This study has been carried out in Mardin province to determine the prevalence of exposure to domestic violence among women aged between 15-49 years and the affecting factors. The population of the study consisted of the women aged between 15-49 years living in Mardin and 1111 people were selected for sampling. Through repeated visits, 1064 people were included in the study (the responsiveness rate was 95.8%). x² (chi-square) test was used in the statistical analysis. The average age of women was 32.5 ± 8.2. 29.4% of them were illiterate. 47.5% of them were married by prearrangement. 25.9% of them were subjected to physical violence by their father and 37.6% by their mother in the past. The women were exposed to physical (44.5%), verbal/emotional (56.4%), economic (37.7%), and sexual violence (14.8%) at least once in their lifetime. 13.2% of them are still exposed to domestic physical violence, 15.8% to verbal/emotional violence, and 7.3% to sexual violence. As the educational levels, socioeconomic status, and monthly income of women and their husbands decrease, the rate of exposure to violence increases (p <0.05). The factors such as being married by bride exchange and bride price, having a familial history of honor killing, living with a co-wife, experiencing childhood violence, having an alcoholic and gambling husband increase the rate of exposure of women to violence (p <0.05). Domestic violence against women was found to be significantly high in Mardin province. Considering the socio-economic and cultural conditions of the region, legal and social regulations should be enforced in cooperation with non-governmental organizations, public institutions as well as local and national press.
Keywords: Sosyal Çalışma; Kriminoloji ve Ceza Bilimi; Sağlık Politikaları ve Hizmetleri